A Systematic Literature Review On Magnesium Oxide As Expansive Agent In Self Healing Concrete - Low, Phak Ho (Universiti Sains Malaysia, 2021)
This dissertation presents a systematic literature review about the magnesium oxide (MgO) in the self-healing concrete. The objectives of this review is to appraise the effectiveness of MgO as an agent for self-healing concrete. Besides, this review also identify and evaluate the sequence findings in the application of MgO in self-healing concrete and identify the gap of knowledge in the application of MgO as an expansive agent for self-healing concrete. For the information, self-healing concrete can heal the crack automatically without any external intervention to regain strength and durability. Yet, the expansion behaviour of MgO in the concrete helped to fill the crack. Therefore, there were 17 articles had been identified in this review from the Scopus database. Systematic searching strategies had been used to screen out the irrelevant articles and the article quality assessment also being used to avoid the publications of poor methodological quality. In this review, the calcination system, reactivity of MgO and nano-MgO were discussed. Results showed that the calcination temperature and holding time will directly affect the reactivity of MgO. Then, relationship between MgO and the other minerals such SCM or curing additive were investigated, and the results showed that the combination of mineral and MgO showed better performance than the individual MgO. In addition, the application method and AMD environment for concrete with MgO were studied. The MgO incorporation in concrete in most environment condition generally decreases the strength and shrinkage but improved the load recovery and durability indicator such as higher crack area reduction, low gas permeability and water absorption. Furthermore, the diffusion of healing agent and characteristic of pellet were the main issue to be manipulated in order not to affect the concrete’s properties as well as maintain the self-healing behaviour.